World economic survey, 1973 : part one. population and development - United Nations (New York : United Nations Publication, 1973)
This book contains a comprehensive details of world economic conditions published by the United Nations.
asm 23/01/2019
Ref.
Keywords: Economic history; International economics; Futuring; Cooperation; Economic conditions; Trade, International